PODATEK OD NIERUCHOMOŚCI JAKO PRZEDMIOT KONFLIKTÓW MIĘDZY GMINAMI I PŁATNIKAMI (STUDIUM PRZYPADKU) - Grabowiecka, Weronika; Słodowa-Hełpa, Małgorzata (Wydział Prawa i Administracji UAM, 2004)
Real estate tax constitutes one of the main items in the local taxation system, especially if we consider its impact on shaping the local economy as well as tax revenue. It is the most important and most efficient local tax, applying to a wide range of entities. It is also homogenous in terms of type o f property taxed and applies the same criteria to physical and legal persons. The last couple of years have seen conflicts concerning the issue of real estate tax. Since 1996 these conflicts have been resolved by the Supreme Court of Administration. The idea of applying a real estate tax to mine sites is a vexed issue both in terms of jurisprudence and doctrine.
REAL ESTATE TAX DETERMINATION AS A POINT OF CONTENTION BETWEEN MUNICIPALITIES AND TAXPAYERS (CASE STUDY)